Characteristics of diabetic foot disease and risk factors in Benghazi, Libya - Buzaid, Najat; Nagem, Fatma (Ibnosina Journal of Medicine and Biomedical Sciences, 2018)
Introduction: Diabetic foot ulcer and amputation are associated with an increased incidence of morbidity and mortality. Diabetic foot ulcer can be prevented by screening for risk factors and proper interventions. Objectives: We aimed to determine the risk of diabetic foot ulcer and amputation among patients with type 2 diabetes at Benghazi Medical Center diabetic clinic. Patients and Methods: A cross-sectional study of diabetic foot status and risk factors in diabetic patients attending a specialist diabetes clinic in Benghazi, Libya. Results: Eighty-seven (84.5%) patients wear inappropriate shoes, 37 (35.9%) had Tinea pedis, 26 (25.2%) had foot deformity, 13 (12.6%) patients had bilateral hallux valgus deformity, 8 (7.8%) patients had clawing of feet, 2 (1.9%) patients had Charcot joint, and one patient (0.97%) had amputated toes. Dorsalis pedis and posterior tibial arteries pulsations were not palpable in six (5.8%) patients, there was a loss of protective sensation among 20 (19.4%) patients, vibration sense was absent in 15 (14.6%) patients, and joint position sense was lost in five (4.9%) patients. According to Scottish Intercollegiate Guideline Network system, 59 (57.3%) patients were in the low-risk category, 18 (17.5%) were in the moderate-risk, 22 (21.4%) were in the high-risk, and 4 (3.9%) were in the active disease categories. Conclusions: We conclude that the prevalence of diabetic foot risk factors is high among the studied group.
Keywords: Benghazi; diabetes; foot; risk; ulcer